The genome of Gallaecimonas pentaromativorans strain 10A, isolated from a Pacific oyster, sheds light on an environmentally widespread genus with remarkable metabolic potential - Yasmine Gouin; Adam Wilcockson; Amy M. Chan; Curtis A. Suttle; Kevin Xu Zhong (PLoS ONE, 2025)
Bacteria in the genus Gallaecimonas are known for their ability to breakdown complex hydrocarbons, making them of particular ecological and biotechnological significance. However, few species have been isolated to date, and their ecological distribution has yet to be examined. Here, we report a novel strain of G. pentaromativorans , designated as strain 10A, which was isolated from a Pacific oyster ( Magallana gigas , a.k.a. Crassostrea gigas ) collected from a farm experiencing a mass mortality event in British Columbia (BC), Canada. Gallaecimonas pentaromativorans strain 10A is a rod-shaped, motile bacterium and has a circular genome of 4,322,156 bp encoding 3,928 protein-coding sequences (CDS). Phylogenetic analysis showed that strain 10A is closely related to members of G. pentaromativorans. Like other Gallaecimonas members, strain 10A is predicted to harbor specific pathways involved in degrading xenobiotic compounds including polycyclic aromatic hydrocarbons (PAHs), producing biosurfactants, and assimilating nitrate and sulfate; however, it is uniquely equipped with an additional 166 genes belonging to 147 protein families, including a putative higB - higA that likely contributes to enhanced stress response. Strain 10A also possesses Clustered Regularly Interspaced Short Palindromic Repeat (CRISPR) and CRISPR-associated (Cas) system (CRISPR-Cas), prevalent in Gallaecimonas (detected in three out of four species), implying a potential defense mechanism against exogenous mobile genetic elements such as plasmids and viruses. We also mined publicly available databases to establish the widespread distribution of bacteria in the genus Gallaecimonas in seawater, sediments, and freshwater across latitude, suggesting its versatility and importance to environmental processes. Ultimately, this study demonstrates that the genome of G. pentaromativorans strain 10A, isolated from a Pacific oyster, may encode a suite of putative functions, including xenobiotic breakdown, biosurfactant production, and CRISPR-Cas defense. This plasticity and breadth in metabolic function help to explain the cosmopolitan distribution of members of this genus.